Positive electrode for solid-state battery and solid-state battery

A lithium-ion conductive oxide coating on the positive electrode of all solid lithium batteries addresses electrolyte deterioration by reducing direct contact and moisture absorption, enhancing battery resistance and performance.

JP7622716B2Active Publication Date: 2025-01-28TOYOTA JIDOSHA KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022140486
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-05
Publication Date
2025-01-28
Estimated Expiration
2042-09-05

AI Technical Summary

Technical Problem

The sulfide solid electrolytes in all solid lithium batteries deteriorate due to direct contact with positive electrode active material particles, leading to increased battery resistance, which is exacerbated by moisture absorption during storage and use.

Method used

A positive electrode for all solid batteries is coated with a lithium-ion conductive oxide coating membrane, ensuring a high NOX ratio on its surface to inhibit direct contact and reduce moisture absorption, thereby maintaining low resistance.

Benefits of technology

The coating significantly reduces battery resistance by minimizing direct contact and moisture absorption, resulting in a positive electrode with improved performance and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622716000002
    Figure 0007622716000002
  • Figure 0007622716000003
    Figure 0007622716000003
  • Figure 0007622716000004
    Figure 0007622716000004
Patent Text Reader

Abstract

To provide a positive electrode for an all-solid battery with low resistance.SOLUTION: A positive electrode for an all-solid battery has a sulfide solid electrolyte and a coating active material. The coating active material includes a positive electrode active material particle and a coating film for covering a surface of the positive electrode active material particle at least partially. The coating film includes a lithium ion conductive oxide and includes NOx in at least a surface. A rate of NOx in the surface of the coating film is higher than 1000 ppm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode for an all-solid-state battery and to an all-solid-state battery. [Background technology]

[0002] In an all-solid-state lithium battery (sulfide-based all-solid-state battery, hereinafter abbreviated as "all-solid-state battery") using a lithium ion conductive solid electrolyte (sulfide solid electrolyte), if the sulfide solid electrolyte comes into direct contact with positive electrode active material particles, etc., the sulfide solid electrolyte may deteriorate. If the sulfide solid electrolyte (ion conductive path) deteriorates, the battery resistance may increase. Therefore, it has been proposed to form a coating film on the surface of the positive electrode active material particles. The coating film prevents direct contact between the positive electrode active material particles and the sulfide solid electrolyte, thereby suppressing the deterioration of the sulfide solid electrolyte.

[0003] The coating material is lithium niobate (LiNbO 3 Lithium ion conductive oxides such as LiNbO 3 etc. have a relatively high resistance.

[0004] Japanese Patent No. 6311630 (Patent Document 1) discloses an active material having a nitrogen-containing lithium niobate layer on its surface, in which the ratio (CN / CNb) of the nitrogen element concentration (CN) to the niobium element concentration (CNb) on the surface of the lithium niobate layer is 0.08 or more and 0.53 or less. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6311630 Summary of the Invention [Problem to be solved by the invention]

[0006] In order to reduce the resistance of all-solid-state batteries, a drying process is carried out to reduce the amount of moisture in the active material, which is the cause of increased resistance. However, there is a risk that moisture will be re-adsorbed by the active material during storage of the dried active material or inside the all-solid-state battery, causing an increase in resistance.

[0007] An object of the present disclosure is to provide a positive electrode for an all-solid-state battery having low resistance. [Means for solving the problem]

[0008] [1] A positive electrode for an all-solid-state battery comprising a sulfide solid electrolyte and a coated active material, the coated active material includes positive electrode active material particles and a coating film that covers at least a portion of a surface of the positive electrode active material particles, the coating film contains a lithium ion conductive oxide and contains NOx at least on its surface; A positive electrode, wherein the ratio of NOx on the surface of the coating film is higher than 1000 ppm.

[0009] In the positive electrode of [1] above, the ratio of NOx 21 on the surface of the coated active material 1 (coating film 2) is high. Since water 22 is difficult to adsorb to NOx, the high ratio of NOx reduces the amount of water adsorbed to the active material (see FIG. 1). This suppresses an increase in the resistance of the positive electrode, and a positive electrode with low resistance can be obtained.

[0010] [2] The positive electrode according to claim 1, wherein the ratio of NOx on the surface of the coating film is 1050 ppm or more and 1500 ppm or less.

[0011] If the ratio of NOx on the surface of the coating film is too high, the NOx can become a resistance during charging and discharging, which can increase the resistance of the positive electrode. Therefore, in the positive electrode of [2] above, by keeping the NOx ratio within a specific range, resistance can be more reliably reduced.

[0012] [3] The positive electrode according to [1], wherein a ratio of the water content to the NOx content on the surface of the coating film is less than 1.90.

[0013] The positive electrode of [3] above has a high ratio of NOx on the surface of the coating film, and therefore has a low moisture content in the active material, and therefore has low resistance.

[0014] [4] The positive electrode according to [3], wherein a ratio of the moisture content to the NOx content on the surface of the coating film is 0.7 to 1.8.

[0015] If the ratio of the moisture content to the NOx content on the surface of the coating film is too low, the resistance of the positive electrode may increase. Therefore, in the positive electrode described above [4], the ratio of the moisture content to the NOx content is within a specific range, thereby more reliably reducing resistance.

[0016] [5] An all-solid-state battery comprising the positive electrode according to any one of [1] to [4]. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a schematic cross-sectional view for explaining a coated active material used in a positive electrode of the present disclosure. [Diagram 2] 1 is a graph showing the relationship between the H2O / NOx ratio and the positive electrode resistance in each of Examples 1 and 2 and Comparative Example 1. [Diagram 3] FIG. 1 is a cross-sectional view illustrating a configuration of an all-solid-state battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure.

[0019] In this specification, elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only "one particle" but also "an aggregate of particles (powder, powder, particle group)."

[0020] If the compound has a stoichiometric formula (e.g., LiCoO 2 When a stoichiometric formula is expressed by a formula such as "LiCoO ", the stoichiometric formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, lithium cobalt oxide may be expressed by a formula such as "LiCoO 2 ", unless otherwise specified, the lithium cobalt oxide is not limited to a composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping with trace elements, substitution, etc. may also be permitted.

[0021] <Positive electrode> The positive electrode of this embodiment is a positive electrode for an all-solid-state battery that includes a sulfide solid electrolyte and a coated active material. First, the coated active material used in this positive electrode will be described, and the configuration of the positive electrode other than the coated active material will be described later in the description of the all-solid-state battery.

[0022] [Coated active material] 1, the coated active material 1 includes positive electrode active material particles 10 and a coating film 2. The coated active material 1 can be referred to as, for example, a "coated positive electrode active material."

[0023] The coated active material 1 may, for example, form an aggregate. That is, one coated active material 1 may contain two or more positive electrode active material particles 10. The coated active material 1 may have a D50 of, for example, 1 to 50 μm, may have a D50 of 1 to 20 μm, or may have a D50 of 5 to 15 μm.

[0024] In this specification, "D50" refers to the particle size at which the cumulative frequency from the smaller particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method.

[0025] <Coating film> The coating film 2 covers at least a portion of the surface of the positive electrode active material particles 10 .

[0026] The coating film 2 contains a lithium ion conductive oxide and contains NOx at least on its surface.

[0027] The lithium ion conductive oxide is an oxide having lithium ion conductivity. The lithium ion conductive oxide may be, for example, an oxide containing lithium and an element other than lithium. Examples of the lithium ion conductive oxide include lithium niobate (LiNbO 3 ) can be preferably used. The Li composition ratio in the lithium ion conductive oxide is, for example, 2.5 or less. Note that, as long as the lithium ion conductive oxide has lithium ion conductivity, the Li composition ratio may be zero.

[0028] (NOx ratio) The ratio of NOx (NOx ratio) on the surface of the coating film 2 (coated active material 1) is higher than 1000 ppm. The ratio of NOx on the surface of the coating film 2 is preferably 1050 ppm or more and 1500 ppm or less, more preferably 1050 ppm or more and 1400 ppm or less. below , more preferably 1100 ppm or more and 1400 ppm or more below , more preferably 1100 ppm or more and 1300 ppm or more below , more preferably 1100 ppm or more and 1250 ppm or more below It is.

[0029] The ratio of NOx on the surface of the coated active material can be measured by elemental analysis using XPS, for example, in the same manner as in the Examples described later. Note that the ratio of NOx measured by XPS in this embodiment is the ratio of NOx on the surface of the coating film. This ratio is a value that reflects the ratio of NOx in the coating film (overall in the thickness direction), but is not equivalent thereto.

[0030] (H 2 O / NOx ratio) The ratio of the moisture content in the coated active material to the NOx ratio (H 2 The O / NOx ratio is preferably smaller than 1.90, more preferably 0.7 to 1.8, even more preferably 1.2 to 1.7, and even more preferably 1.3 to 1.7.

[0031] The moisture content in the coated active material can be measured by TPD-MS in the same manner as in the Examples described later.

[0032] In the coated active material 1, the coverage of the coating film 2 on the surface of the positive electrode active material particle 10 may be, for example, 70% or more. A coverage of 70% or more is expected to reduce the battery resistance. The coverage may be, for example, 85% or more, 88% or more, 89% or more, 90% or more, 94% or more, 95% or more, or 97% or more. The coverage may be, for example, 100% or less, or 99% or less. The coverage may be, for example, 85 to 97%, or 90 to 97%. The coverage may also be measured by XPS.

[0033] The coating film 2 may have a thickness of, for example, 5 to 100 nm, 5 to 50 nm, 10 to 30 nm, or 20 to 30 nm.

[0034] The thickness of the coating film can be measured by the following procedure. A sample is prepared by embedding the coated active material in a resin material. The sample is subjected to a cross-section processing using an ion milling device. For example, an ion milling device manufactured by Hitachi High-Technologies Corporation under the product name Arblade (registered trademark) 5000 (or an equivalent product) may be used. The cross-section of the sample is observed using a SEM (Scanning Electron Microscope). For example, an SEM device manufactured by Hitachi High-Technologies Corporation under the product name SU8030 (or an equivalent product) may be used. For each of the 10 coated active materials, the film thickness is measured in 20 fields of view. The arithmetic average of the film thicknesses at a total of 200 points is regarded as the film thickness.

[0035] 《Cathode active material particles》 The positive electrode active material particle 10 is the core of the coated active material 1. The positive electrode active material particle 10 may be a secondary particle (aggregation of primary particles). The positive electrode active material particle 10 (secondary particle) may have a D50 of, for example, 1 to 50 μm, may have a D50 of 1 to 20 μm, or may have a D50 of 5 to 15 μm. The primary particle may have a maximum Feret diameter of, for example, 0.1 to 3 μm.

[0036] The positive electrode active material particles 10 may contain any component. The positive electrode active material particles 10 may contain, for example, LiCoO 2 , LiNiO 2 , LiMnO 2 , LiMn 2 O 4 , Li(NiCoMn)O 2 , Li(NiCoAl)O 2 , and LiFePO 4 For example, "Li(NiCoMn)O 2 "(NiCoMn)" in "Li(NiCoMn)O" indicates that the sum of the composition ratios in the parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. 2 For example, Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O 2, Li(Ni 0.5 Co 0.2 Mn 0.3 )O 2 , Li(Ni 0.8 Co 0.1 Mn 0.1 )O 2 etc. may be included.

[0037] <All-solid-state battery> 3 is a conceptual diagram showing an all-solid-state battery in this embodiment. The all-solid-state battery 100 includes a positive electrode 3, a separator layer 5, and a negative electrode 4.

[0038] The all-solid-state battery 100 may include, for example, an exterior body (not shown). The exterior body may be, for example, a pouch made of a metal foil laminate film. The exterior body may house a power generating element including the positive electrode 3, the separator layer 5, and the negative electrode 4.

[0039] 《Positive electrode》 The positive electrode 3 is layered. The positive electrode 3 may include, for example, a positive electrode active material layer 31 and a positive electrode current collector 32. For example, the positive electrode active material layer 31 may be formed by applying a material for the positive electrode active material layer to the surface of the positive electrode current collector 32. The positive electrode current collector 32 may include, for example, an Al foil or the like. The positive electrode current collector 32 may have a thickness of, for example, 5 to 50 μm.

[0040] The positive electrode active material layer 31 may have a thickness of, for example, 10 to 200 μm. The positive electrode active material layer 31 is in close contact with the separator layer 5. The positive electrode active material layer 31 includes a coated active material (coated positive electrode active material) and a sulfide solid electrolyte. Details of the coated active material are as described above.

[0041] The sulfide solid electrolyte can form an ion conduction path in the positive electrode active material layer 31. The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, with respect to 100 parts by volume of the coated active material (coated positive electrode active material). The sulfide solid electrolyte contains S. The sulfide solid electrolyte may contain, for example, Li, P, and S. The sulfide solid electrolyte may further contain, for example, O, Si, or the like. The sulfide solid electrolyte may further contain, for example, a halogen, or the like. The sulfide solid electrolyte may further contain, for example, iodine (I), bromine (Br), or the like. The sulfide solid electrolyte may be, for example, a glass ceramic type or an argyrodite type. The sulfide solid electrolyte may be, for example, LiI-LiBr-Li 3 P.S. 4 , Li 2 S-SiS 2 , LiI-Li 2 S-SiS 2 , LiI-Li 2 SP 2 S 5 , LiI-Li 2 O-Li 2 SP 2 S 5 , LiI-Li 2 SP 2 O 5 , LiI-Li 3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 , and Li 3 P.S. 4 may contain at least one selected from the group consisting of:

[0042] For example, "LiI-LiBr-Li 3 P.S. 4 " is LiI, LiBr and Li 3 P.S. 4 The sulfide solid electrolyte may be produced by mixing Li and Li in any molar ratio. For example, the sulfide solid electrolyte may be produced by a mechanochemical method.2 SP 2 S 5 " is Li 3 P.S. 4 Includes: 3 P.S. 4 For example, Li 2 S and P 2 S 5 And "Li 2 S / P 2 S 5 = 75 / 25 (molar ratio)".

[0043] The positive electrode active material layer 31 may further include, for example, a conductive material. The conductive material can form an electronic conduction path in the positive electrode active material layer 31. The blending amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the coated active material. The conductive material may include any component. The conductive material may include, for example, at least one selected from the group consisting of carbon black, vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake.

[0044] The positive electrode active material layer 31 may further include, for example, a binder. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the coated active material. The binder may include any component. The binder may include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), styrene butadiene rubber (SBR), and polytetrafluoroethylene (PTFE).

[0045] 《Negative electrode》 The negative electrode 4 is layered. The negative electrode 4 may include, for example, a negative electrode active material layer 41 and a negative electrode current collector 42. For example, the negative electrode active material layer 41 may be formed by applying a material for the negative electrode active material layer to the surface of the negative electrode current collector 42. The negative electrode current collector 42 may include, for example, a Cu foil, a Ni foil, or the like. The negative electrode current collector 42 may have a thickness of, for example, 5 to 50 μm.

[0046] The negative electrode active material layer 41 may have a thickness of, for example, 10 to 200 μm. The negative electrode active material layer 41 is in close contact with the separator layer 5. The negative electrode active material layer 41 includes negative electrode active material particles and a sulfide solid electrolyte. The negative electrode active material layer 41 may further include a conductive material and a binder. The sulfide solid electrolyte may be the same or different between the negative electrode active material layer 41 and the positive electrode active material layer 31. The negative electrode active material particles may include any component. The negative electrode active material particles may be, for example, graphite, Si, SiO x (0 <x<2)、およびLi 4 Ti 5 O 12 may contain at least one selected from the group consisting of:

[0047] <Separator layer> The separator layer 5 is interposed between the positive electrode 3 and the negative electrode 4. The separator layer 5 separates the positive electrode 3 from the negative electrode 4. The separator layer 5 includes a sulfide solid electrolyte. The separator layer 5 may further include a binder. Between the separator layer 5 and the positive electrode active material layer 31, the sulfide solid electrolyte may be the same or different. Between the separator layer 5 and the negative electrode active material layer 41, the sulfide solid electrolyte may be the same or different.

[0048] <Method of manufacturing coated active material> The method for producing a coated active material in this embodiment includes “(a) preparation of a mixture” and “(b) production of a coated active material.” This production method may further include, for example, “(c) heat treatment” or the like.

[0049] (a) Preparation of the mixture The present manufacturing method includes preparing a mixture by mixing a coating liquid with positive electrode active material particles (applying the coating liquid to the surfaces of the positive electrode active material particles). Details of the positive electrode active material particles are as described above.

[0050] The mixture may be, for example, a suspension or a wet powder, and it is sufficient that the coating liquid is attached to the surface of the positive electrode active material particles in the mixture. For example, a suspension may be formed by dispersing the positive electrode active material particles (powder) in a coating liquid. For example, a wet powder may be formed by spraying the coating liquid into a powder containing the positive electrode active material particles. In this manufacturing method, any mixing device, granulating device, etc. may be used.

[0051] The coating liquid contains a solute (including a solute and a dispersoid) and a solvent (including a solvent and a dispersion medium or a solvent).

[0052] In this embodiment, NH 3 It is preferable to add water. This can increase the amount of NOx in the coating film. However, the method of increasing the amount of NOx in the coating film is not limited to this. For example, adding lithium nitrate (LiNO 3 ) may be blended, and NOx may be adsorbed onto the coated active material covered with the coating film by the flow of NOx gas.

[0053] The solute includes the raw material of the coating film, such as the lithium ion conductive oxide described above. The total amount of the solutes may be, for example, 0.1 to 20 parts by mass, 1 to 15 parts by mass, or 5 to 10 parts by mass relative to 100 parts by mass of the solvent.

[0054] The solute may further contain Li, for example, a lithium compound such as lithium hydroxide, lithium carbonate, lithium nitrate, etc.

[0055] The solvent may contain any component as long as the solute dissolves in the solvent. The solvent may contain, for example, water, alcohol, etc. The solvent may contain, for example, ion-exchanged water, etc.

[0056] (b) Production of coated active material The present manufacturing method includes drying the mixture to manufacture a coated active material. The coating solution attached to the surface of the positive electrode active material particles is dried to produce a coating film, thereby manufacturing the coated active material. In the present manufacturing method, any drying method can be used.

[0057] When the mixture is a suspension containing positive electrode active material particles and a coating liquid, the coated active material may be formed, for example, by a spray-drying method. That is, the suspension containing positive electrode active material particles and a coating liquid is sprayed from a nozzle, and the sprayed droplets are dried, for example, by hot air, to form the coated active material. By using the spray-drying method, for example, an improvement in the coverage rate is expected.

[0058] The solid content of the suspension for spray drying may be, for example, 1 to 50% or 10 to 30% by volume. The nozzle diameter may be, for example, 0.1 to 10 mm or 0.1 to 1 mm. The hot air temperature may be, for example, 100 to 200°C.

[0059] For example, the coated active material may be produced by a tumbling fluidized bed coating apparatus. In the tumbling fluidized bed coating apparatus, "(a) Preparation of the mixture" (adhesion of the coating liquid to the surface of the positive electrode active material particles) and "(b) Production of the coated active material" can be carried out simultaneously.

[0060] (c) Heat Treatment The present manufacturing method may include subjecting the coated active material to a heat treatment. The coating film may be fixed by the heat treatment. The heat treatment may also be called "firing". In the present manufacturing method, any heat treatment device may be used. The heat treatment temperature may be, for example, 150 to 300°C. The heat treatment time may be, for example, 1 to 10 hours. For example, the heat treatment may be performed in air or in an inert atmosphere. EXAMPLES

[0061] <Comparative Example 1> [Preparation of coated active material] 100 parts by mass of hydrogen peroxide solution (mass concentration: 30%) was added to the container. Next, 113.4 parts by mass of ion-exchanged water and 5.1 parts by mass of niobium oxide [Nb 2 O 5 3H 2 Next, 10.1 parts by mass of ammonia water (mass concentration: 28%) was added to the container. The contents of the container were thoroughly stirred to prepare a solution. Furthermore, 1.2 parts by mass of lithium oxide (Li 2 O.H. 2 O) was dissolved in a solution to prepare a coating solution.

[0062] Positive electrode active material particles: LiNi 0.8 Co 0.15 Al 0.05 O 2 A suspension was prepared by dispersing 100 parts by mass of the positive electrode active material particles in 53.8 parts by mass of the coating liquid. The suspension was spray-dried to prepare a powder of the coated active material.

[0063] The obtained coated active material was heat-treated in an air atmosphere. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. As a result, a coated active material (coated positive electrode active material) having a coating film with a thickness of about 10 nm was obtained. In this coated active material, the coating film was made of lithium niobate (LiNbO 3 ) is considered to be included.

[0064] [Fabrication of all-solid-state batteries] (Preparation of positive electrode) The following materials were prepared: Sulfide solid electrolyte: Li 2 SP 2 S 5 Glass-ceramics Conductive material: Carbon nanotubes Binder: SBR (styrene butadiene rubber) Dispersion medium: 1,2,3,4-tetrahydronaphthalene Positive electrode collector: Aluminum foil

[0065] The coated active material, the sulfide solid electrolyte, the conductive material, the binder, and the dispersion medium were mixed to prepare a positive electrode slurry. Positive electrode slurry In contrast, the amount of coated active material (positive electrode active material) was 81.2 parts by mass, the amount of sulfide solid electrolyte was 16.5 parts by mass, the amount of conductive material was 1.9 parts by mass, and the amount of binder was 0.3 parts by mass.

[0066] The positive electrode slurry was thoroughly stirred using an ultrasonic homogenizer (UH-50, manufactured by SMT). The positive electrode slurry was applied to the surface of the positive electrode current collector to form a coating film. The coating film was dried at 100°C for 30 minutes using a hot plate. In this way, a positive electrode blank was produced. A positive electrode was cut out from the positive electrode blank.

[0067] (Preparation of negative electrode) In the kneading vessel of the Filmix device, a sulfide solid electrolyte (sulfide glass solid electrolyte: Li 2 SP 2 S 5 The negative electrode active material (Li-based glass ceramics), the conductive additive (carbon nanotubes), the binder (SBR: styrene butadiene rubber), and the solvent (diisobutyl ketone) were added and stirred. 4 Ti 5 O 12 The mixture (particles) was placed in a kneading vessel and stirred with a Filmix device to prepare a negative electrode mixture slurry.

[0068] Relative to 100 parts by mass of the material for the negative electrode active material layer (excluding the solvent), the amount of the negative electrode active material was 72.2 parts by mass, the amount of the sulfide solid electrolyte was 24.3 parts by mass, the amount of the conductive material was 2.4 parts by mass, and the amount of the binder was 1.8 parts by mass.

[0069] The prepared negative electrode mixture slurry was applied onto a negative electrode current collector (Ni foil) and dried for 30 minutes at 100° C. Thus, a negative electrode blank was produced. A negative electrode was cut out from the negative electrode blank.

[0070] (Preparation of separator) In the kneading vessel of the Filmix device, a sulfide solid electrolyte (sulfide glass solid electrolyte: Li 2 SP 2 S 5 A separator mixture slurry was prepared by adding a mixture of a cellulose acetate-based glass ceramic, a binder (ABR: acrylate butadiene rubber), and a solvent (a mixture of n-heptane and butyl butyrate) and stirring them with a Filmix device.

[0071] The blending amount of the sulfide solid electrolyte was 99.6 parts by mass, and the blending amount of the binder was 0.4 parts by mass, relative to 100 parts by mass of the separator material (excluding the solvent).

[0072] The prepared separator mixture slurry was applied onto a substrate (Al foil) and dried for 30 minutes at 100° C. Thus, a separator blank was produced. A separator of the same size as the negative electrode was cut out from the separator blank.

[0073] (Battery Construction) A positive electrode is placed on one side of the separator, and a negative electrode is placed on the other side of the separator, and a pressure of 6 ton / cm is applied. 2 Then, with the terminals (tab leads) inserted in the positive and negative electrodes, the specimens were pressed with a pressure of 1 ton. Energy storage element was produced. The power storage element was covered with a laminate film to produce an all-solid-state battery (small laminate cell).

[0074] <Example 1> The coating solution is NH 3 This is thought to be one of the reasons why NOx exists in the coating film. In Example 1, in order to increase the amount of NOx in the coating film, 39.0 mg of NH 3 Water was added. NH 3 The water concentration was 14 to 15 mass %. In this manner, the coating liquid was prepared. The coated active material, positive electrode and battery of Example 1 were produced in the same manner as in Comparative Example 1 except for the above.

[0075] Specifically, NH was 0 mg in Comparative Example 1, 39.0 mg in Example 1, and 220.0 mg in Example 2. 3 Water was added.

[0076] <Example 2> In Example 2, in order to further increase the amount of NOx in the coating film, 220.0 mg of NH was added to 26.0 to 26.5 g of the coating solution. 3 Added water. In all other respects, the coated active material, positive electrode, and battery of Example 2 were produced in the same manner as in Example 1.

[0077] <Evaluation> [Measurement of NOx ratio on the surface of coated active material (coating film)] For each of the coated active materials (coated positive electrode active materials) of the above-mentioned Examples and Comparative Examples, the NOx ratio on the surface of the coated active material was measured. Specifically, elemental analysis was performed on the surface of the coating film by XPS according to the following procedure, and the NOx ratio was calculated from the obtained elemental analysis results.

[0078] An XPS instrument is prepared. For example, an XPS instrument manufactured by ULVAC-PHI, Inc., called "Product name: PHI X-tool" (or an equivalent product) may be used. A sample powder of the coated active material is set in the XPS instrument. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. For example, analysis software manufactured by ULVAC-PHI, Inc., called "Product name: MulTiPak" (or an equivalent product) may be used. The ratio of NOx on the surface of the coated active material (coating film) is calculated from the peak area (integral value) of the NOx spectrum.

[0079] [Measurement of Moisture Content of Coated Active Material] The moisture content of each of the coated active materials of the above Examples and Comparative Examples was measured. The moisture content of the coated active material is measured by TPD-MS (Temperature Programmed Desorption-Mass Spectrometry) by measuring the integrated moisture concentration (integrated moisture content) generated from the coated active material when the coated active material is heated from 25°C (room temperature) to 500°C. The moisture content of the coated active material is the ratio of the integrated moisture content to the total mass of the coated active material (excluding moisture). The unit of moisture content is "ppm" (wtppm). The TPD-MS measuring device is configured by connecting a mass spectrometer (MS) to a special heating device with a temperature controller, and can track the change in concentration of gas generated from a sample heated according to a set heating program as a function of temperature or time.

[0080] [Measurement of battery output resistance after durability test (charge / discharge evaluation)] For each of the batteries (all-solid-state batteries) produced in the above examples and comparative examples, the output resistance of the battery after the durability test was measured. Specifically, activation, capacitance measurement, resistance measurement, endurance test, capacitance measurement (after the endurance test), and resistance measurement (after the endurance test) were performed in this order. Battery activation, capacity and resistance measurements were carried out at 25°C. The cell confinement pressure was 5 MPa relative to the electrode area.

[0081] (activation) The battery was activated by performing constant current-constant voltage (CC-CV) charging at a 1 / 3C rate (0.333C-0.01C cut upper limit 2.7V) and CC-CV discharging (0.333C-0.01C cut lower limit 1.5V) in that order.

[0082] (Capacitance measurement) For each battery, one cycle of CC-CV charging and CC-CV discharging was performed in the same way as for activation. The discharge capacity was confirmed as the battery capacity. "C" is the unit of current rate. "1C" indicates the current rate at which the SOC (State of Charge) reaches 100% from 0% by charging for one hour.

[0083] (Measurement of discharge resistance) The batteries with the above confirmed capacities were charged at a rate of 1 / 3 C until the SOC (state of charge) reached 75, 40 or 20%. After that, the voltage change (ΔV) when a current of 2.5 C was applied (discharged) was measured, and the resistance (discharge resistance) was calculated using Ohm's law (V=IR).

[0084] The above-mentioned capacity and resistance measurements were also performed on the batteries after a durability test (trickle test, upper limit voltage: 2.7 V, 2 weeks, 60° C.).

[0085] The measurement results of the discharge resistance after the durability test (ratio when the discharge resistance of Comparative Example 1 is set to 1.00) are shown in Table 1. Note that the smaller the discharge resistance, the higher the output characteristics (discharge rate) of the battery.

[0086] [Table 1]

[0087] From the results shown in Table 1, it can be seen that in Examples 1 and 2, where the ratio of NOx is high, the increase in the resistance of the positive electrode (battery) is suppressed. This is because in Examples 1 and 2, the water content and H 2 This is believed to be due to a decrease in the O / NOx ratio.

[0088] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]

[0089] 1 coated active material, 10 positive electrode active material particles, 20 coating film, 21 NOx, 22 water (H 2 O), 3 positive electrode, 31 positive electrode active material layer, 32 positive electrode current collector, 4 negative electrode, 41 negative electrode active material layer, 42 negative electrode current collector, 5 separator layer (solid electrolyte layer).

Claims

1. A positive electrode for an all-solid-state battery comprising a sulfide solid electrolyte and a coated active material, the coated active material includes positive electrode active material particles and a coating film that covers at least a portion of a surface of the positive electrode active material particles, the coating film contains a lithium ion conductive oxide and contains NOx at least on its surface; The ratio of NOx on the surface of the coating film is higher than 1000 ppm and is 1500 ppm or less; A positive electrode, wherein the ratio of the moisture content to the NOx content on the surface of the coating film is less than 1.

90.

2. 2. The positive electrode according to claim 1, wherein the ratio of NOx on the surface of the coating film is 1050 ppm or more.

3. 2. The positive electrode according to claim 1, wherein a ratio of a moisture content to a NOx content on the surface of the coating film is 0.7 to 1.

8.

4. An all-solid-state battery comprising the positive electrode according to claim 1.

Citation Information

Patent Citations

  • Lithium battery positive electrode material, preparation method thereof and all-solid-state lithium battery

    CN111864188A

  • Production of nitrogen-containing cermet

    JP1988011630A

  • Solid electrolyte for sodium-sulfur battery and manufacture thereof

    JP1991088276A

  • Active material composite particle and lithium battery

    JP2016170973A

  • Active material composite particle, electrode active material layer, and all-solid lithium battery

    JP2016207567A